The Effectiveness of the Application of Rock Painting Activities in Developing the Creativity of Children aged 5-6 Years in Kindergarten - Mayolanda Hesti; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
The study was set back by the low the creativity of children age 5-6 years in the Adzkia Air Bangis. one of the key factors this is suspected because it is not suitable or the media used by the teacher is not interestig. This study aims to determine the effectiveness of the application of rock painting activities in developing the creativity of children aged 5-6 years in kindergarten Adzkia Air Bangis. the type of research is quantitative usng pseudo-experiment methods (quasi experiment) with pre-test design and post-test. The research population is 55 people. While the sampel 10 children. Sampling retrieval techniques are used sampling samples. The data uses t-test samples samples. As a result of the coclusion to the data collaction and management, 1) before being given an treatment (pre-test) the development of children’s creativity can be categorized as starting to develop but has not developed as expected. This is based on the result of research by researchers at Adzkia Air Bangis Kindergarten 2) after being given treatment (post-test) the development of chidren’s creativity can be categorized as developing according to expectations. 3) there is significant difference between the result of the pre-test and post-test after doing the paired sampe t-test sig 0,000 < 0,05.  Advice for teachers helping teachers by using experimental learning methods to develop the creativity of children aged 5-6 years trough rock painting activities.